Phenomenology Study of Youth Victims of Bullying Coping Experience At Public High School Banda Aceh City - Rizka Humeira; Asniar Asniar; Suryane Sulistiana Susanti (Universitas STRADA Indonesia, 2021)
Violence among youths has emerged in many schools in recent years. One form of violence that occurs in schools is acts of violence or what is often referred to as bullying.This type of research is qualitative with a phenomenological approach and uses data collection methods with in-depth interviews. Participants in this study were youth victims of bullying who were obtained based on purposive sampling technique. The results of this study identified 5 themes, tolerating vs rejecting bullying, being subjected to unpleasant treatment, showing strength, keeping busy with positives and receiving protection vs lost support. Researchers suggest the need for schools to provide more indepth socialization about bullying and be able to evaluate the progress of each student to avoid the impact of bullying, and schools can work together with related agencies such as health centers to overcome bullying problems experienced by teenagers in school.